(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
This study aimed to describe the pedagogical practices of elementary educators as well as divulge their lived encounters as they promote numeracy skills of students in the midst of the pandemic. This study employs a descriptive approach. Results indicated that Elementary teachers have a variety of experiences upon promoting numeracy skills of students in light of the new educational landscape brought by the COVID-19 pandemic; these pedagogical practices need to be suitable in the new context in education